Potential Therapeutic Functions of PU-91 and Quercetin in Personalized Cybrids Derived from Patients with Age-Related Macular Degeneration, Keratoconus, and Glaucoma - Nasim Salimiaghdam; Lata Singh; Mithalesh Kumar Singh; Marilyn Chwa; Shari Atilano; Zahra Mohtashami; Anthony Nesburn; Baruch D. Kuppermann; M. Cristina Kenney (MDPI AG, 2023)
The aim of this study is to investigate the therapeutic potential of higher doses of PU-91, quercetin, or in combination on transmitochondrial cybrid cell lines with various mtDNA haplogroups derived from patients with age-related macular degeneration (AMD), glaucoma (Glc), keratoconus (KC), and normal (NL) individuals. Cybrids were treated with PU-91 (P) (200 µM) alone, quercetin (Q) (20 µM) alone, or a combination of PU-91 and quercetin (P+Q) for 48 h. Cellular metabolism and the intracellular levels of reactive oxygen species (ROS) were measured by MTT and H2DCFDA assays, respectively. Quantitative real-time PCR was performed to measure the expression levels of genes associated with mitochondrial biogenesis, antioxidant enzymes, inflammation, apoptosis, and senescence pathways. PU-91(P) (i) improves cellular metabolism in AMD cybrids, (ii) decreases ROS production in AMD cybrids, and (iii) downregulates the expression of LMNB1 in AMD cybrids. Combination treatment of PU-91 plus quercetin (P+Q) (i) improves cellular metabolism in AMD, (ii) induces higher expression levels of TFAM, SOD2, IL6, and BAX in AMD cybrids, and (iii) upregulates CDKN1A genes expression in all disease cybrids. Our study demonstrated that the P+Q combination improves cellular metabolism and mitochondrial biogenesis in AMD cybrids, but senescence is greatly exacerbated in all cybrids regardless of disease type by the P+Q combined treatment.